Efek Suplementasi Madu terhadap Penurunan Frekuensi Diare Akut pada Anak di RSUD Dr. H. Abdul Moeloek Bandar Lampung - Nidia Putri Meisuri; Roro Rukmi Windi Perdani; Hanna Mutiara; Asep Sukohar (Majority, 2020)
Diarrheal diseases is still health problems of the world with high number of mortality and morbidity. Traditional medicine which has a bitter taste and antibacterial effect, one of which has the effect of antibacterial honey, bitter taste and antioxidants. This study to find out the potential effects of honey supplementation on reducing the frequency of acute diarrhea in children in the Dr. H. Abdul Moeloek. This study used quasi-experimental design with nonequivalent control group design. Subjects of study were children with acute diarrhea who were divided into two intervention groups and control group, each group amounted to 15 respondents. Data obtained directly from research subjects through primery data. From the data obtained then the analysis is performed using unpaired samples t-test. This study indicates the frequency of first-day acute diarrhea of intervention group was more than control group. The frequency of acute diarrhea on the second, third and fourth days in intervention group was less than children who were controls group. The statistical test results show the potential effects of honey supplementation on decreasing frequency of acute diarrhea. Provision of honey supplementation was proven to reduce the frequency of acute diarrhea in the Dr. H Abdul Moeloek Hospital Bandar Lampung.